A COMPARATIVE STUDY ON THE VIEWS OF KARL BARTH AND EMIL BRUNNER ON NATURAL THEOLOGY AND ITS RELEVANCE TODAY - Amos, Jesse S. (QUAERENS: Journal of Theology and Christianity Studies, 2024)
The purpose of this research is, by investigation into the views of Barth and Brunner on natural theology, to restate and emphasize its relevance for us today—in the first quarter of the twenty-first century. This is achieved via a comparative analysis—by which this research adopts the purely objective method as well as the critical theological analysis and biblical assessment. It is by design naturalistic, which means it is non- manipulative. The research-maintained neutrality and attentiveness to dynamics. The analysis is inductive; given each case its unique orientation, holistic perspective, and context sensitivity. Barth denied that God can be known outside of Christ. This is to say, he is against general revelation but only accepts special revelation. Brunner insists that there is a knowledge of God obtainable in nature — though dimmed as it may be serves as a point of contact between God and man. He accepts general revelation, but it is subservient to special revelation. The position reached in this research agrees more with Brunner, that: natural theology is relevant in that, we can make the most positive use of it for doing theology and witnessing Christ—in our time. While most works on natural theology rests merely on its importance in apologetics, this work have taken it farther, at least, for evangelistic purposes.